2013
DOI: 10.1902/jop.2012.110708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Diode Laser Therapy as an Adjunct to Non‐Surgical Periodontal Treatment: A Randomized Clinical Study

Abstract: The present study indicates that, compared to SRP alone, multiple adjunctive applications of a 980-nm diode laser with SRP showed PD improvements only in moderate periodontal pockets (4 to 6 mm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 28 publications
7
86
2
Order By: Relevance
“…This result was controversial to studies conducted by Moritz A et al, Dukic et al, that showed a significant improvement [23,24]. This conflicting result may be due to the higher power settings and multiple radiations used in those studies.…”
Section: Discussionmentioning
confidence: 88%
“…This result was controversial to studies conducted by Moritz A et al, Dukic et al, that showed a significant improvement [23,24]. This conflicting result may be due to the higher power settings and multiple radiations used in those studies.…”
Section: Discussionmentioning
confidence: 88%
“…9 Group I showed statistically significant difference than group II on comparing moderate attachment loss at 7th day only, which may be due to greater retraction of periodontal tissues in the laser group and this achieved stability by 30th day. 28 In our study, diode laser led to significant improvement of clinical parameters (PD, RAL, BOP) after 30 days compared with that of SRP alone, Dukic 13 The beneficial effects of nonsurgical laser therapy to treat periodontal diseases have been discussed in many studies and reviews. 35,36 These could be due to better subgingival debridement of the pocket and eradication of periodontal microorganism within the subgingival area.…”
Section: Discussionmentioning
confidence: 55%
“…26 Moderate pockets were reduced only in group I which was also found by various studies. 12,13,16,17,23,27 We observed that this reduction was more so at 30th day and was not seen at 7th day which may be indicative of healing period of the treated pocket. 28 The reduction in PD can be due to the availability of new site for the attachment of connective tissue.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Laser can be classified according to its lasing medium (solid or gas), wavelength (390-700 nm) and tissue applicability (hard tissue and soft tissue). 2 Based on different characteristics, laser has a variety of indication in dentistry including non-surgical sulcular debridement, 3 hard tissue ablation, 4 soft tissue removal, 5 gingival depigmentation, 5,6 ablation of aphthous ulceration 7 and pain reduction. 8 Numerous studies have focused on laser as an adjunctive procedure in orthodontic practice.…”
Section: Introductionmentioning
confidence: 99%